Concordance between sudomotor disorder and the clinical diagnosis of diabetic peripheral neuropathy, according to various clinical guidelines. - Chicharro-Luna, Esther; Ortega-Ávila, Ana Belén; Requena-Martínez, Aránzazu; Gijón-Noguerón, Gabriel (Elsevier, 2021)
Aim To assess the concordance between variations in Neuropad® results and the those in different diagnostic criteria of Diabetic Peripheral Neuropathy, according to various clinical guidelines. Methods A descriptive observational study was conducted of 111 patients with a confirmed diagnosis of diabetes mellitus. The criteria for inclusion in the study were that patients should be aged 18 years or more and have at least 10 years’ history of diabetes mellitus. Results 73 (65.8%) were male and 38 (34.2%) were female. Their mean age was 57.92 ± 13.24 years (95% CI 55.45–60.38). Healthy Neuropad® findings were obtained for 35 right feet (31.5%) and 31 left feet (27.9%). Conclusion Neuropad® is an effective instrument for detecting macro and microvascular complications such as early-stage neuropathy, although its use should always be accompanied by a clinical examination of the foot.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/16932
Keywords: Neuropatía diabética; Nervios periféricos - Enfermedades; Clinical guidelines; Diabetic peripheral neuropathy; Diabetes mellitus; Neuropad